The health rehabilitators’ professional development and family education - Pérez Cardero, Bertha Karina (Transformación, 2024)
Objective: This paper aims at describing a model of health rehabilitators’ development focusing family education and counseling to face attention/hyperactivity syndrome. Methods: The authoress follows a quantitative-qualitative researching approach based on document reviewing (Hernádez-Sampieri et at., 2018), and systematization of contents (Expósito & González, 2017; y Mera, 2019). Likewise, she relies on interviewing, surveying and modeling to devise an innovative model of health rehabilitators’ development. Results: The main result of the study is a pedagogical model of professional improvement of the health rehabilitator characterized by the expansion of the performance of this professional to the affective and volitional spheres through the guidance of the patient’s family as a way to prevent mental retardation disorder. attention/hyperactivity.Conclusions: The improvement of the health rehabilitator can be improved by expanding its objectives and content focused on the guidance of the patient’s family as a way to prevent attention deficit/hyperactivity disorder.